Dehydroepiandrosterone and sport - Corrigan, B. (The Medical Journal of Australia, 1999)
Dehydroepiandrosterone (DHEA) is a weak androgen, but is one of the main precursors of testosterone. Athletes use it for its androgenic and anticatabolic effects and it has been described as a "wonder drug", although there is little evidence to support these claims. There are no published studies of the long term effects of taking DHEA, particularly in the large doses used by athletes, or of its possible interactions with other agents.